Higher education management and operational research : demonstrating new practices and metaphors - Bell, Gary; Warwick, Jon; Galbraith, P. (Peter) (Educational futures, 2012)
Higher Education in the UK operates in a rapidly changing and highly complex environment. Universities need to adapt quickly to this environment and managers must begin to explore 'new angles' and approaches in addressing the challenges they are now facing. This book offers a tool box of metaphors and associative Operational Research (OR) approaches. Metaphors are a powerful 'way of seeing' but also 'a way of not seeing'. Furthermore, the OR discipline has significantly evolved over the last 30 years which has led to the emergence of three distinctive intellectual areas, namely Hard OR, Soft OR and Methodological Pluralism OR. Drawing on these intellectual areas and on the experience of educational and OR practitioners, the book highlights the use of various OR approaches to a variety of complex and uncertain problems encountered in higher education management. The book aims to explore 'new perspectives' in HE management thinking and to describe and illustrate the use of OR methodologies, methods and techniques in helping HE managers to make informed management decisions.